PI3K/mTOR inhibitor omipalisib prolongs cardiac repolarization along with a mild proarrhythmic outcome in the AV block dog model - van Bavel, J. J. A.; Pham, C.; Beekman, H. D. M.; Houtman, M. J. C.; Bossu, A.; Sparidans, R. W.; van der Heyden, M. A. G.; Vos, M. A. (Frontiers in Cardiovascular Medicine, 2022)
Background The phosphoinositide 3-kinase (PI3K) signaling pathway is an interesting target in cancer treatment. The awareness of the proarrhythmic risk of PI3K inhibitors was raised because PI3K is also involved in regulating signaling toward cardiac ion channels. Canine cardiomyocytes treated with PI3K inhibitors show an increased action potential duration and reduced cardiac repolarizing currents. Now, the potential proarrhythmic effect of chronic treatment of PI3K/mTOR inhibitor GSK2126458 (omipalisib) was investigated in the atrioventricular (AV) block dog model. Methods Purpose-bred Mongrel dogs received complete AV block by ablation of the bundle of His and their hearts were paced in the right ventricular apex at VDD-mode (RVA-VDD). In this way, sinus rhythm was maintained for 15 ± 1 days and thereby bradycardia-induced cardiac remodeling was prevented. Dogs received 1 mg/kg omipalisib once (n = 3) or twice (n = 10) a day via oral administration for 7 days. Under standardized conditions (anesthesia, bradycardia at 60 beats/min, and a dofetilide challenge), potential proarrhythmic effects of omipalisib were investigated. Results Twice daily dosing of omipalisib increased accumulative plasma levels compared to once daily dosing accompanied with adverse events. Omipalisib prolonged the QT interval at baseline and more strongly after the dofetilide challenge (490 ± 37 to 607 ± 48 ms). The arrhythmic outcome after omipalisib resulted in single ectopic beats in 30% of dogs perpetuating in multiple ectopic beats and TdP arrhythmia in 20% of dogs. Isolated ventricular cardiomyocytes from omipalisib-treated dogs showed a diminished IKs current density. Conclusion Chronic treatment of PI3K/mTOR inhibitor omipalisib prolonged the QT interval in a preclinical model under standardized proarrhythmic conditions. Furthermore, this study showed that electrical remodeling induced by omipalisib had a mild proarrhythmic outcome.